Implications of physiological changes in pregnancy in COVID-19 - Rosales-Campos, Rolando Dario; Pérez-Hernández, Héctor José; Acosta-Brooks, Soraida Cándida (Revista 16 de abril, 2022)
Pregnant women generally constitute a group at high risk of infectious diseases due to gestational immunological and physiological changes in their system. That is why the objective of this work is to analyze the implications of the physiological changes of pregnancy in SARS-CoV-2 disease. Physiological changes in pregnant women not only increase their susceptibility to the virus, but also increase the severity of the disease. Changes in the respiratory and immune systems, the role of the placenta in coagulation, and the function of endothelial cells are the physiological changes that most influence the disease. The decrease in lung capacity and the variations that occur in the immune system represent new treatment challenges for pregnant women with COVID-19 disease and therefore new areas of research limited so far.